Impact of aging on the overall liking and sensory characteristics of sourdough breads and comparison of two methods to determine their sensory shelf life. Issue 10 (17th September 2020) - Gauchez, Hélène; Loiseau, Anne‐Laure; Schlich, Pascal; Martin, Christophe
Abstract : Abstract: The objectives of the present work were to study the evolution of the sensory properties and overall liking of four sourdough breads over their lifespans and to determine their sensory shelf life (SSL). We also intended to identify the main sensory characteristics leading to a decrease in overall liking and the end of the consumption of the breads. Seventy‐eight consumers evaluated different 1 kg sourdough breads at home. Two methods were used to describe the evolution of the sensory properties and overall liking: one based on ratings of descriptors' intensities and the other based on the magnitude of the changes observed since the previous consumption. As expected, the results showed that sensory properties and liking scores evolved over time. While the aroma and taste properties changed little, the texture deteriorated significantly. The overall liking scores decreased steadily over time, while the percentage of subjects who stopped eating bread increased. "Easiness to cut with the teeth, " "easiness to chew, " "crispness, " and "softness" were the main characteristics positively correlated with the overall liking scores and negatively correlated with the percentage of rejection. In contrast, "dryness of the crumb" was negatively correlated with the liking scores and positively correlated with the percentage of rejection. A survival analysis determined that the SSL (50% rejection) of the breads was approximately 2.5 days. Interestingly, we highlighted that the average liking score corresponding to the SSL was just below the middle of the overall liking scale. Practical Application: The results of this work could be of interest to bread‐making professionals who will be able to use the main conclusions to advise their clients and possibly adapt the bread format to their sensory shelf life. This work was also an opportunity to highlight sourdough bread, which offers more flexibility than French baguette in managing the consumption of the bread purchased. The alternative approach tested to measure the evolution of sensory characteristics and overall liking could interest the professionals of sensory analysis.